Personality Development and Religion of Maturity - Kadankavil, Thomas (Journal of Dharma, 1985)
Many are the ways in which religion could be subjected to a scienti- fic study. Together with the discipline of the Philosophy of Religion, religion is studied from historical, anthropological, sociological and cultural points of view. Again with the Comparative Methodology (1856) of Max Muller, the discipline of Comparative Study of Religions also began to develop. Contemporaneous with these attempts, Psycho- logy also focussed its attention on religion. The last two decades of the nineteenth century and the first quarter of the twentieth were mar- ked by a special determination to apply the modern critical and empiri- cal methods to the study of religion. During this period vigorous attempts have been made to use the resources of Scientific Psychology in the investigation of religion. Under the title "Psychology of Reli- gion" a number of studies have been conducted, using psychological and psychoanalytic insights, to understand and interpret religious be- haviour or experience in general and religious beliefs, symbols and practices in particular. On the other hand 'Religious Psychology, addressed itself to the task of discovering the place of religion in the life-economy of the individual.